Decision support system for urban sustainability planning in Malaysia - Ahris Yaakup; Siti Zalina Abu Bakar; Susilawati Sulaiman (Environmental Management Society, Malaysia, 2009)
Development planning requires an effective approach to achieve the desired goals and objectives, evaluate alternative as well as control development programs that are in line with current and future prospects. In the quest toward urban sustainability planning, a support tool in the form of an information system is required for enhancing analyses and deriving rational decisions. Planning support system (PSS) and decision support system (DSS) are among the tools for achieving quality planning for optimum development. They support the tasks of plan formulation, monitoring and review which inevitably involve the assembly and integration of geographic information and are known to be widely used in considering alternative spatial development strategies as well as assessing development potentials involved in land use planning. This article discusses various uses of DSS with a focus on its functionalities in supporting development planning and management at various levels